2015
DOI: 10.1016/j.eucr.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Rare Renal Incidentaloma in Pregnancy: An Unusual Primitive Neuroectodermal Tumor Presentation

Abstract: Peripheral Primitive Neuroectodermal Tumors (PNETs) are rare lesions that arise from outside the central nervous system and normally do not affect the genitourinary system. Primary renal presentations are extremely rare but given their aggressive behavior and characteristic cytomorphologic and genetic features should be considered well-defined distinct clinical entities in order to distinguish them from other primary tumors featuring round cells in the kidney. We report one case of PNET involving the kidney an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…PNET/EWS in pregnant patients is extremely rare with few case reports in publication discovered during our literature review [ 12 ]. Sites of origin have included the brain, pancreas, ovary, and cervix, with a select number of recent case reports with primary renal tumors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNET/EWS in pregnant patients is extremely rare with few case reports in publication discovered during our literature review [ 12 ]. Sites of origin have included the brain, pancreas, ovary, and cervix, with a select number of recent case reports with primary renal tumors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…PNET/EWS in pregnant patients is extremely rare with few case reports in publication discovered during our literature review [ 12 ]. Sites of origin have included the brain, pancreas, ovary, and cervix, with a select number of recent case reports with primary renal tumors [ 12 ]. Pregnancy represents a unique state in terms of immune function as the mother's body must seek to balance protection from foreign antigens and infections with tolerance of the foreign fetal antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Our case was the largest PNET ever reported, and we observed that the tumor grew rapidly during pregnancy and even spontaneous rupture occurred. Some reports show that PNET enlargement is more obvious during pregnancy ( Torga et al, 2015 ; Miao et al, 2018 ). However, the association between the change of hormones during pregnancy and tumor growth needs further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, most features of this neoplasm have been presented through case reports and there are few original articles in this context (6)(7)(8). Based on the literature reviewed, less than 100 cases of PNET of kidney have been reported to date.…”
Section: Discussionmentioning
confidence: 99%